Uncovering subclinical cardiotoxicity across chemotherapy phases in pediatric oncology - Aurensanz-Clemente, Esther; Garcia-Canadilla, Patricia; Gorostegui, Maite; Rivera, Cristina; Clara Escobar-Díaz, María; Randanne, Paula; Morales La Madrid, Andres; Sanchez-de-Toledo, Joan (Frontiers in Oncology, 2025)
Background and objectivesAdvances in cancer therapies have significantly improved survival rates in children. However, treatment-related toxicities remain common. This study aims to evaluate the incidence and characteristics of cardiotoxicity in a pediatric cancer cohort.MethodsThis prospective study included pediatric patients who received chemotherapy between September 2020 and March 2023. Patients were categorized into five groups according to treatment phase: baseline, early treatment, late treatment, end-of-treatment, and relapse. Cardiovascular evaluation included anthropometric assessment, laboratory biomarkers, electrocardiogram (ECG) and functional echocardiography. Patients were stratified for cardiotoxicity according to pediatric and adult clinical practice guidelines.Results265 patients were included (mean age 9.95 ± 5.26 years). The incidence of ventricular dysfunction was 2.3%. A decline in LVEF > 10% from baseline was observed in 16.5% of patients. Abnormal global longitudinal strain (GLS) values were found in 34.7%; significant ECG changes in 16.2%, and elevated Troponin I levels in 7.1%. Based on echocardiographic and laboratory findings, patients undergoing treatment showed greater cardiac involvement compared with those in other groups.ConclusionsAlthough the overall incidence of overt ventricular dysfunction was low, the use of ECG and GLS enhanced the sensitivity for detecting of subclinical cardiac impairment in pediatric patients receiving chemotherapy.